Development of Science and Practical Activities at Pillar University - Galina M. Konovalova; Galina D. Bryukhanova; Elena K. Vorobey; Evgenia V. Vidishcheva; Alexander N. Volkov; Andrey S. Kopyrin (Высшее образование в России)
The article presents the mechanisms, regional effects and the model of refocusing scientific and practical activities of Sochi State University from fragmentary research in certain areas of applied science (in the past) to complex interdisciplinary projects. These projects are being implemented since the university was granted a status of a pillar university in Krasnodar territory and aimed at ensuring sustainable development of Sochi and the region as a whole. As a result of the implementation of the flagship strategic project “Expert-Analytical Center ‘Agency of Modern Technologiesfor SustainableTourism’”, an interdisciplinary expert-analytical,scientific, consulting, and information-communication environment has been formed at Sochi State University in order to increase the efficiency of cooperation between government, business, local consumers and tourist services, as well asto overcome the barriersto the socio-economic development ofthe region and to the natural balance between the generations.The aim isto develop and putinto practice the measurable quantities of forecasting processes in the system “nature – economy – society – man” for the subsequentspreading of acquired experience to other territories.The implementation ofthe project stimulated the growth of university credibility with the regional representatives of the innovation community and allowed to increase the number of industrial partners, the amount of R & D funded from extrabudgetary sources to 82%, including 43% of small and medium businesses.